2016
DOI: 10.1007/978-3-319-42445-3
|View full text |Cite
|
Sign up to set email alerts
|

Handbook of Eudaimonic Well-Being

Abstract: part of the material is concerned, specifi cally the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfi lms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…Per definition, character strengths contribute to individuals' fulfillment, flourishing, and thriving (Peterson and Seligman 2004). Accordingly, research has shown meaningful relations between specific character strengths and favorable outcomes in different areas of life, including physical health, life satisfaction, psychological well-being, and young people's school achievement and vocational orientation (e.g., Harzer 2016;Park et al 2004;Proyer et al 2012Proyer et al , 2013Weber 2018).…”
Section: Cognitive Strengths That Entail the Acquisition And Use Of Kmentioning
confidence: 99%
See 1 more Smart Citation
“…Per definition, character strengths contribute to individuals' fulfillment, flourishing, and thriving (Peterson and Seligman 2004). Accordingly, research has shown meaningful relations between specific character strengths and favorable outcomes in different areas of life, including physical health, life satisfaction, psychological well-being, and young people's school achievement and vocational orientation (e.g., Harzer 2016;Park et al 2004;Proyer et al 2012Proyer et al , 2013Weber 2018).…”
Section: Cognitive Strengths That Entail the Acquisition And Use Of Kmentioning
confidence: 99%
“…The goal of this special issue is to provide insights into individual and organizational strategies and interventions which may foster individual growth, flourishing, and thriving at work. Individual growth, flourishing, and thriving at work are very broadly construed in this paper, and include improvements in subjective and psychological well-being (Harzer 2016(Harzer , 2017a as well as increases in performance and proficiency on the individual, team, and organizational level (Harzer et al 2017;Harzer und Ruch 2014). The present paper aims to summarize and discuss relevant strategies and interventions on the individual, team, and organizational level to promote the use of character strengths in the workplace, which should in turn increase individual growth, flourishing, and thriving at work.…”
mentioning
confidence: 99%
“…Estos hallazgos, por tanto, son consistentes con nuestra hipótesis de partida y sugieren que las creencias de competencia personal del estudiantado universitario estarían altamente influenciadas por el grado en que los aprendices se consideran hábiles para gestionar las demandas de su día a día (e.g., adaptarse a nuevas exigencias, preparar exámenes y trabajos, hacer nuevas amistades, trabajar con otras personas, vivir alejados de sus familias, etc.) y aprovechar las oportunidades que el contexto les ofrece para satisfacer sus propias necesidades y valores (Ryff, 2016). Sin embargo, la autopercepción de baja capacidad para hacer frente a estas exigencias cotidianas (i.e., bajo dominio del ambiente) podría resquebrajar las expectativas de autoeficacia del estudiantado, lo que, a su vez, podría repercutir negativamente sobre su nivel de implicación académica (Bresó et al, 2005; 6!…”
Section: Discussionunclassified
“…Finalmente, tienen capacidad para elegir o crear contextos apropiados para la satisfacción de las propias necesidades y valores. Por el contrario, las personas con bajo dominio percibido del ambiente tienen dificultades para manejar los acontecimientos cotidianos, se sienten incapaces de cambiar o mejorar su entorno personal, desaprovechan las oportunidades que este proporciona y manifiestan una palpable carencia de percepción de control con respecto al mundo exterior (Ryff, 2016). Partiendo de esta caracterización, resulta plausible hipotetizar que el alumnado que evidencie niveles más elevados de dominio percibido del ambiente desarrollará expectativas de autoeficacia más elevadas.…”
unclassified
“…Therefore, the study of eudaimonia is as critical in 21 st century behavioral science agendas as it was in ancient philosophies [20]. In recent decades, since the emergence and impetus of Positive Psychology [32], more attention has been paid to the study of eudaimonic well-being [33,34], suggesting that it is especially relevant to study its facets related to valuing and fulfilling the mission at work, which help to develop the individual’s identity and self-realization.…”
Section: Introductionmentioning
confidence: 99%